PENGARUH PENGGUNAAN LABORATORIUM VIRTUAL BERBASIS PHET TERHADAP PENGUASAAN KONSEP HUKUM NEWTON PADA SISWA MAN 5 BATANGHARI - Kurniawan, Imam; Sukarno; Purnama , Boby Yasman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of using a PhET-based virtual laboratory on students’ mastery of Newton’s Laws. The research is motivated by students’ low understanding of physics concepts, particularly the abstract nature of Newton’s Laws, which require effective experimental and visualization activities. Limited laboratory facilities at school hinder optimal learning; therefore, alternative instructional media such as PhET-based virtual laboratories are needed. This quantitative study employed a quasi-experimental method with a pretest-posttest control group design. The participants were two classes: an experimental class that used a PhET-based virtual laboratory and a control class that received conventional instruction. The instrument used was a concept mastery test on Newton’s Laws, administered before (pretest) and after instruction (posttest). Data were analyzed using descriptive statistics, hypothesis testing, and N-Gain calculations to measure improvement in students’ conceptual understanding. The results showed that students’ initial mastery of Newton’s Laws was in the low to moderate category. After instruction, both classes demonstrated improvement; however, the experimental class showed greater gains. The N-Gain score of the experimental class was 0.49 (moderate category), while the control class obtained 0.22 (low category). Hypothesis testing indicated a significant difference between the two groups. Thus, the use of a PhET-based virtual laboratory positively affects students’ mastery of Newton’s Laws at MAN 5 Batanghari.